The Effect of GEMAS-Based Learning on Junior High School Students’ Mathematical Problem-Solving Skills Based on Krulik and Rudnick’s Indicators - Ana Setiani; Hamidah Suryani Lukman; Ida Rahmawati; Novi Andri Nurcahyono (RANGE: Jurnal Pendidikan Matematika, 2026)
The PISA 2022 results indicate that Indonesian students’ mathematical performance remains below the OECD average, which calls for instructional innovations that support mathematical problem-solving at the junior high school level. This study examined the use of the Mathematics Educational Game (GEMAS) in supporting students’ mathematical problem-solving skills on linear equations in one variable (LEOV), systems of linear equations in two variables (SLETV), and combined linear equation problems. GEMAS was designed as a game-based learning medium that integrates mathematical tasks with problem-solving stages based on Krulik and Rudnick’s framework, namely read and think, explore and plan, select a strategy, locate and answer, and reflect and extend. This study employed a quantitative approach with a one-group pretest-posttest quasi-experimental design involving 60 students of SMPN 12 Sukabumi in the second semester of the 2024/2025 academic year. The instruments consisted of a mathematical problem-solving test and semi-structured interviews. Data were analyzed using paired-sample t-tests and normalized gain scores. The results showed statistically significant differences between students’ pretest and posttest scores across the three topics: LEOV, SLETV, and combined problems, with moderate normalized gain scores ranging from 0.3901 to 0.5465. These findings suggest that the use of GEMAS was associated with moderate improvement in students’ mathematical problem-solving skills. The study contributes to the development of mathematics educational games by aligning game-based activities with explicit problem-solving indicators, making GEMAS a potential learning medium to support the implementation of the Merdeka Curriculum.